Risk Factor of Stillbirth among Pregnant Women at Dr. Hasan Sadikin General Hospital Bandung from 2017–2020 - David Immanuel; Hadi Susiarno; Windi Nurdiawan (Althea Medical Journal, 2022)
Background: Stillbirth is one of the most devastating pregnancy outcomes that affects approximately 2.6 million pregnancies worldwide. Several factors have been identified to be associated with stillbirth, and grouped based on the pathophysiological aspects, such as maternal, placental, fetal, and unknown or unexplained factors. This study aimed to describe the prevalence, along with the baseline and risk factor characteristics of stillbirth among singleton pregnancies at Dr. Hasan Sadikin General Hospital Bandung. Methods: A descriptive, cross-sectional study design was conducted, including all stillbirth medical records from 2017 to 2020 obtained from the Department of Obstetrics and Gynecology, Dr. Hasan Sadikin General Hospital Bandung. Medical records with complete baseline data, 2nd–3rd trimester pregnancies, and singleton pregnancies were collected.Results: The prevalence of stillbirth cases in this study was 2.2%. Most of the cases occurred in the age range of 20–35 years old (64.4%) with the gestational age of >28 weeks (65.8%). Of all risk factors observed, hypertensive disorders were the most common medical conditions found (45.6%), followed by unknown factors (17.8%), and congenital abnormalities (14.2%).Conclusions: The majority of stillbirth patients are at their optimal reproductive age, nulliparity, and have hypertensive disorders during pregnancy, specifically the superimposed preeclampsia subtype. Although the prevalence is considerably low, early management of the risk factors, particularly hypertensive disorder, is important to prevent its occurrence.